Law Reform on Severance Pay Due to the Global Economic Crisis and the Impact of War: The Value of Justice - Gunarto Gunarto (Jurnal Hukum, 2026)
This study aims to analyze the legal issues related to severance pay arrangements in termination of employment due to the global economic crisis, examine comparative worker protection after termination of employment due to the global crisis, and formulate a legal reconstruction of severance pay funds based on justice. The research method used is doctrinal legal research. The results of the study indicate that severance pay remains a worker's right arising from termination of employment and cannot be replaced by Job Loss Insurance, because Job Loss Insurance only functions as additional protection after termination of employment. The comparative study shows that worker protection can be strengthened through unemployment insurance, vocational training, job placement services, and a special fund for the garment sector collected from export activities. The legal reconstruction of severance pay funds in Indonesia should be directed at establishing mandatory severance savings during employment, providing emergency funds for the garment sector, strengthening Job Loss Insurance benefits, and strict verification of crisis-related reasons used by companies in carrying out layoffs, so that the burden of risk can be shared fairly between workers, employers, and the state.